Forage seed systems to close the ruminant feed deficit in Eastern Africa - Burkart, Stefan; Mwendia, Solomon (MDPI, 2024)
This study examines key challenges and opportunities for improving ruminant productivity in East Africa, with a focus on enhancing access to forage seeds critical for livestock systems in Ethiopia, Tanzania, Kenya, Uganda, Rwanda, and Burundi. Despite high potential for increased livestock production, the region faces a significant feed deficit—nearly 40% of annual feed demand remains unmet—due to the limited availability and affordability of forage seeds. The research identifies a critical gap in quality seed access, with many farmers relying on outdated materials. We propose the promotion of recently improved forage varieties and local seed production as a solution to reduce dependence on costly imports and enhance adoption. Our analysis suggests that bridging the forage deficit would require the cultivation of 2 million hectares and the involvement of 1.5 million farmers, highlighting the scale of intervention needed. Additionally, the regional forage seed market presents an economic opportunity, potentially valued at USD 877 million over the next decade, underlining the importance of government policies, the development of seed systems, and market incentives. The study concludes with recommendations for fostering seed production, improving seed distribution, and addressing socio-economic barriers to ensure widespread adoption and enhance livestock productivity in the region.